2004
DOI: 10.1002/chin.200450100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐Oxo‐2H‐chromene‐3‐carboxylic Acid (5‐Methyl‐3‐isoxazolyl) and (3‐Methyl‐5‐styryl‐4‐isoxazolyl) Amides as Potential Bioactive Compounds.

Abstract: Compounds. -Title compounds (V) and (VII) are prepared from aminoisoxazoles (I) and (VI) respectively by treatment with diethylmalonate (II) followed by cyclization with salicylaldehydes (IV) (no yields given). (Vb) shows significant antibacterial activity against Escherichia coli, Proteus vulgaris, Bacillus mycoides and Staphylococcus aureus and the degree of inhibition is comparable to that of streptomycin. -(RAJANARENDAR*, E.; RAMU, K.; RAMESH, P.; Indian J. Chem., Sect. B: Org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The synthesized compounds are characterized by elemental analysis and spectral studies and evaluated for its antimicrobial activity. Rajanarendar et al [36] reported the synthesis of 2-oxo-2H-chromene-3-carboxylic acid(5-methyl-3-isoxazolyl) and (3-methyl-5-styryl-4-isoxazolyl)amides 41 ( fig. 5) from amino isoxazoles, by treatment with diethyl malonoate followed by cyclization with salicylaldehydes.…”
Section: Fig 3: Structures Of Antimicrobial Isoxazoles 15-23mentioning
confidence: 99%
“…The synthesized compounds are characterized by elemental analysis and spectral studies and evaluated for its antimicrobial activity. Rajanarendar et al [36] reported the synthesis of 2-oxo-2H-chromene-3-carboxylic acid(5-methyl-3-isoxazolyl) and (3-methyl-5-styryl-4-isoxazolyl)amides 41 ( fig. 5) from amino isoxazoles, by treatment with diethyl malonoate followed by cyclization with salicylaldehydes.…”
Section: Fig 3: Structures Of Antimicrobial Isoxazoles 15-23mentioning
confidence: 99%
“…New 3-acylamido coumarins derived from 3-amino-5-substituted isoxazoles (51) have been designed and synthesized for possible anti-microbial agents [130]. Promisingly, Radulovic et al screened a new 3,4-annelated coumarin derivative (52), which showed a greater antibiotic activity than both Ampicillin and Nystatin, and four times as much anti-oxidant activity as -tocopherol acetate [130].…”
Section: Structure Activity Relationships (Sars) Referencementioning
confidence: 99%
“…The dichloroacetamido moiety has also been inserted in to the allylic position of the pyran ring of coumarin, and the resulting compound (50) have moderate activity against B. cirroflagellosus, E. coli, A. niger, and C. albicans [129]. New 3-acylamido coumarins derived from 3-amino-5-substituted isoxazoles (51) have been designed and synthesized for possible anti-microbial agents [130]. Promisingly, Radulovic et al screened a new 3,4-annelated coumarin derivative (52), which showed a greater antibiotic activity than both Ampicillin and Nystatin, and four times as much anti-oxidant activity as -tocopherol acetate [130].…”
Section: Structure Activity Relationships (Sars) Referencementioning
confidence: 99%